Reposisi Literasi Kearsipan dalam Lanskap Transformasi Digital - Sanbein, Primus (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2026)
Digital transformation has fundamentally reshaped the nature of archives, not only in terms of technological media but also in how archives are understood, interpreted, and accounted for. In this context, archival literacy is often narrowly framed as a set of technical skills or individual competencies, a perspective that inadequately captures the complexity of digital archives that are dynamic, distributed, and embedded in contemporary information practices. This article aims to reframe archival literacy as a conceptual lens within the landscape of digital transformation. Adopting a reflective and conceptual approach, the article situates archival literacy within information literacy discourse while examining shifts in the nature of archives in the digital environment. It proposes an understanding of archival literacy as a layered construct encompassing reflective ways of thinking, institutional capacity, and epistemic foundations. The discussion demonstrates that archival literacy should not be treated as a supplementary element of digital transformation, but rather as a conceptual prerequisite that shapes its quality and direction. This reframing underscores the role of archival literacy in sustaining context, meaning, and accountability of digital archives as integral to institutional memory and legitimacy.